Analisis Muqabalah Dalam Al-Qur’an Surah Al-Hadid Dan Desain Pembelajarannya - Siti Khairunisa; Fachrul Ghazi; Amirudin; Guntur Cahya Kesuma (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2026)
Balaghah as a branch of Arabic rhetoric, plays a significant role in revealing the linguistic beauty and depth of meaning in the Qur'an, particularly through the rhetorical device of muqabalah. However, the teaching of muqabalah tends to remain theoretical and has not been fully integrated contextually with Qur’anic text analysis. This study aims to analyze the forms and rhetorical functions of muqabalah in Surah Al-Hadid and to design a balaghah learning model based on its verses. The research employs a qualitative approach with a library research method. The primary data consist of the verses of Surah Al-Hadid, analyzed using linguistic-rhetorical and pedagogical approaches, supported by classical exegetical works such as Tafsir Ibn Kathir and Tafsir al-Munir. The findings reveal various forms of muqabalah, including itsnain bi itsnain, tsalatsah bi tsalatsah, arba’ah bi arba’ah, khamsah bi khamsah, and sittah bi sittah, which emphasize theological and moral messages through semantic contrasts. Based on these findings, a contextual and analytical learning design is proposed to enhance students’ rhetorical understanding and comprehensive verse interpretation.